Kesantunan Berbahasa Guru dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Muliani, Mertiza Fitri; Manaf , Ngusman Abdul; Tressyalina, Tressyalina (UIR Press, 2026)
This study aims to describe and analyze the application of Leech's politeness maxims in teacher speech in Indonesian language learning in fifth grade students of SD IT Ar-Rasyid, Alahan Panjang, West Sumatra. The subject of the study was a fifth grade teacher with 19 students. The study used a qualitative approach with descriptive methods. The data were in the form of teacher's oral speech recorded during two hours of learning, then transcribed and analyzed using the Miles and Huberman interactive analysis model. The validity of the data was guaranteed through diligent observation and rechecking of the recording transcripts thoroughly. The results showed that teachers applied Leech's six politeness maxims with varying frequencies. From the teacher's transcribed speech, the sympathy maxim was the most dominant (7 utterances), followed by the wisdom maxim and the agreement maxim (5 utterances each), the praise maxim and the generosity maxim (3 utterances each), and the humility maxim (2 utterances). The contribution of this research lies in two things: first, the expansion of the study of teacher language politeness to the elementary school level, which has not been studied specifically. Second, the analysis of the phenomenon of Minangkabau language code mixing as a politeness strategy rooted in the local cultural context, which shows that the application of Leech's maxim does not occur in a neutral linguistic space but is modified by the cultural values ​​of the speakers. This study concludes that teacher language politeness is a teacher strategy to create effective, conducive, and character-based learning in elementary schools.